IMPLEMENTATION OF PROVINCIAL GOVERNMENT POLICY ON THE MENTAL HEALTH SECTOR IN PREVENTING SUICIDE CASES IN GORONTALO PROVINCE - Muda, Lisdawati (International Journal of Health Science & Medical Research, 2024)
The increasing number of suicide cases in Gorontalo shows the emergence of mental health problems in the community. The suicide perpetrators consist of adults, parents, and some even minors. The perpetrators committed this careless act due to various cause-and-effect factors such as Lack of love for parents, romance, economic factors, and so on. In addition, the perpetrators of suicide are not only women who are known as weak people but also carried out by men. Even the level of education and career owned by the perpetrators seems to no longer be able to prevent their desire to commit suicide. This condition should require serious attention from all stakeholders, especially the provincial government and all levels of society, considering that suicides occur in almost all districts and cities in Gorontalo province. The implementation of local government policies and actions is an inseparable part of efforts to realize development programs in the health sector, especially in the field of mental health, so that mental disorders or illnesses can be immediately detected and treated to minimize suicide as a sign of mental illness that occurs in the social environment. The research method used is a qualitative method of interviewing respondents. The conclusion is that many factors cause suicide, so it is essential to get a lot of attention from various parties, especially the local government.